2018
DOI: 10.1097/jcn.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mother-Daughter Relationship on Hypertension Self-management and Quality of Life

Abstract: The mothers' perceived relationship quality with daughters directly impacted their own self-management of HTN and HRQOL while also indirectly affecting their daughters' self-management. Similarly, the daughters' perceived strength of their relationship with their mothers directly influenced their self-management and HRQOL and indirectly affected their mothers' self-management and HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…On a first level of evidence for interdependence, research on nonspousal caregiving dyads has shown that good psychological functioning of care recipients, and specific personality traits and intellectual abilities of both caregivers and care recipients (i.e., intrapersonal variables) might impact reciprocal emotional and relational wellbeing of dyad members (Hollis-Sawyer, 2001;Kim et al, 2008;Romano et al, 2020). Moreover, one element of dyadic interdependence strongly reported in a number of studies synthesized in this review was relationship processes (i.e., interpersonal variables) such as communication patterns and dyadic behavioral responses to care may be associated with different levels of dyad members' wellbeing (e.g., quality of life, caregiver burden, depressive symptoms, and relationship quality) (Martini et al, 2001;Heid et al, 2016;Shawler et al, 2018;Bouldin et al, 2019). In line with studies investigating relationship processes of spouses dealing with various illnesses (Laurenceau et al, 1998;Lepore, 2004;Manne and Badr, 2008;Hagedoorn et al, 2011b), our findings suggest that, for example, a shared perception of the quality of the caregiving relationship as well as collaboration, open communication, and positive dyadic responses to care might increase wellbeing outcomes for both members of non-spousal caregiving dyads (Heid et al, 2016;Shawler et al, 2018;Bouldin et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…On a first level of evidence for interdependence, research on nonspousal caregiving dyads has shown that good psychological functioning of care recipients, and specific personality traits and intellectual abilities of both caregivers and care recipients (i.e., intrapersonal variables) might impact reciprocal emotional and relational wellbeing of dyad members (Hollis-Sawyer, 2001;Kim et al, 2008;Romano et al, 2020). Moreover, one element of dyadic interdependence strongly reported in a number of studies synthesized in this review was relationship processes (i.e., interpersonal variables) such as communication patterns and dyadic behavioral responses to care may be associated with different levels of dyad members' wellbeing (e.g., quality of life, caregiver burden, depressive symptoms, and relationship quality) (Martini et al, 2001;Heid et al, 2016;Shawler et al, 2018;Bouldin et al, 2019). In line with studies investigating relationship processes of spouses dealing with various illnesses (Laurenceau et al, 1998;Lepore, 2004;Manne and Badr, 2008;Hagedoorn et al, 2011b), our findings suggest that, for example, a shared perception of the quality of the caregiving relationship as well as collaboration, open communication, and positive dyadic responses to care might increase wellbeing outcomes for both members of non-spousal caregiving dyads (Heid et al, 2016;Shawler et al, 2018;Bouldin et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, daughters who understood their mothers' care needs and costs of being helped had more satisfied mothers (Martini et al, 2001). Perceived strength of the caregiving relationship in a longitudinal study, was found to be associated with dyad members' physical and mental wellbeing over time, with higher perceived strength of the relationship at baseline, in both caregivers (i.e., daughters) and care recipients (i.e., mothers with hypertension), associated with higher overall health related quality of life at 6 months (Shawler et al, 2018). Communication patterns were also found to be associated with different levels of care recipients' depressive symptoms reported by both caregivers (i.e., daughters, sons, siblings, or friends) and care recipients (Bouldin et al, 2019), with caregiving dyads defined as "collaborative" (i.e., frequent positive interactions between caregivers and care recipients) experiencing fewer depressive symptoms.…”
Section: Associations Between Intra/interpersonal Variables and Wellb...mentioning
confidence: 88%
See 2 more Smart Citations
“…Traditionally in literature focused on caregiving, caregivers are conceptualized as a dyad comprised of a patient and their spouse, or their parent and their adult child (Bidwell et al, 2015;Ferro & Boyle, 2015;Shawler, Edward, Ling, Crawford, & Rayens, 2018). From a systems perspective, however, individuals living with chronic conditions are imbedded within a broader social environment that extends beyond a single informal primary caregiver.…”
Section: The Human Factors Perspective Macroergonomics Approach To Elmentioning
confidence: 99%